The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/srep10861
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-mediated strain effect on the role of thermal heating and electric field on metal-insulator transition in vanadium dioxide nanobeams

Abstract: Single-crystalline vanadium dioxide (VO2) nanostructures have recently attracted great attention because of their single domain metal-insulator transition (MIT) nature that differs from a bulk sample. The VO2 nanostructures can also provide new opportunities to explore, understand, and ultimately engineer MIT properties for applications of novel functional devices. Importantly, the MIT properties of the VO2 nanostructures are significantly affected by stoichiometry, doping, size effect, defects, and in particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…5c), revealing that the Joule heating that leads to a local temperature increase may be the primary mechanism driving the IMT in the VO 2 nanowire device. 39,40…”
Section: Effects Of Temperature On Compositional Transition Of Vo 2 Nmentioning
confidence: 99%
“…5c), revealing that the Joule heating that leads to a local temperature increase may be the primary mechanism driving the IMT in the VO 2 nanowire device. 39,40…”
Section: Effects Of Temperature On Compositional Transition Of Vo 2 Nmentioning
confidence: 99%
“…It is suggested that the appearance of the M2 phase in the course of SPT of VO 2 films strongly depends on aspects like crystalline orientation and grain size because they dominate the combined effect of stress on a particular c R -axis direction. 42 We elucidate that in a highly strained (020)-oriented VO 2 film, the appearance of the M2 phase over a wide temperature range is highly unlikely due to the small grain sizes in which the stress effect is relaxed by the grain boundaries. We also show the evolution of the Raman peak intensity of each phase for both (011) and (020)-grains of S3 in Fig.…”
Section: Resultsmentioning
confidence: 86%
“…We adopted the well-known relationship of σ // = −Eε z /2ν, where ν is Poisson's ratio, for deriving the in-plane stress. By using the reported values of Ε and ν of 140 GPa and 0.30, 42,43 a tensile stress of 860 MPa was obtained for the (011)-oriented grains. On the other hand, the peak position of (011) in S3 was almost in accordance with that of the bulk VO 2 , suggesting that the stress on the (011)-oriented grains was relaxed in this sample through the increase of film thickness.…”
Section: Resultsmentioning
confidence: 99%
“…One can see that the critical temperature (T c ), hysteresis width ( H ) and slope of the heating curve (β) are different for the three VO 2 films and their values are summarized in Table II. This is reasonable, as these parameters are typically determined by the substrate [40,[47][48][49] and the film thickness [40,[48][49][50].…”
Section: A Radiative Heat Flux and Emissivitymentioning
confidence: 73%